2018
DOI: 10.18176/jiaci.0272
|View full text |Cite
|
Sign up to set email alerts
|

Association of a 4-Locus Gene Model Including IL13, IL4, FCER1B, and ADRB2 With the Asthma Predictive Index and Atopy in Chinese Han Children

Abstract: Our results indicated that the four-locus gene model consisting of L13 rs20541, IL4 rs2243250, ADRB2 rs1042713 and FCER1B rs569108 was associated with the API and atopy. These findings provide an evidence of the gene model for determining a high risk of developing asthma and atopy in Chinese Han children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Also, the original API was used to explore the effect of a smart nebulizing device on the rate of adherence to ICS in Chinese preschoolers with positive API ( n = 65), showing a significant improve in the rate of adherence, and reducing the frequency of emergency visits and respiratory infections, as well as the usage of antibiotics or systemic steroids (34). A recent study (35) in Chinese Han preschoolers ( n = 385) reported association of four-gene model consisting of IL13 rs20541, IL4 rs2243250, ADRB2 rs1042713, and FCER1B rs569108 with the original API [OR = 4.08, p < 0.0001; and OR = 2.36, p < 0.0001, for stringent and loose API, respectively].…”
Section: Predictive Models For Prognostic or Diagnostic Toolsmentioning
confidence: 99%
“…Also, the original API was used to explore the effect of a smart nebulizing device on the rate of adherence to ICS in Chinese preschoolers with positive API ( n = 65), showing a significant improve in the rate of adherence, and reducing the frequency of emergency visits and respiratory infections, as well as the usage of antibiotics or systemic steroids (34). A recent study (35) in Chinese Han preschoolers ( n = 385) reported association of four-gene model consisting of IL13 rs20541, IL4 rs2243250, ADRB2 rs1042713, and FCER1B rs569108 with the original API [OR = 4.08, p < 0.0001; and OR = 2.36, p < 0.0001, for stringent and loose API, respectively].…”
Section: Predictive Models For Prognostic or Diagnostic Toolsmentioning
confidence: 99%
“…Its pathogenesis is extremely complex. The genes encoding these cytokines determine the occurrence and development of asthma 17 . Therefore, exploring immunological mechanisms underlying childhood asthma as well as identifying biological markers that predict asthma progression is vital for reducing the incidence of childhood asthma and implementing bilevel preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…More risk homozygotes of the four SNPs, higher risk for asthma and atopy 7 . As described in our previous study, the genotype combinations with no risk homozygotes (i.e., rs20541 AA or GA, rs2243250 CC or TC, rs1042713 GG or AG, and rs569108 AA or AG) were considered as the control, and those genotype combinations with a significantly higher risk for asthma and atopy ( p < .05 and odds ratio [OR] > 1) compared with the control were categorized as high risk, otherwise as low risk 8 . Genetic risk grouping was shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Each of the four SNPs had an independent effect on asthma, with rs20541 G, rs2243250 T, rs1042713 A, and rs569108 G as the risk alleles, and more risk homozygotes of the four SNPs, higher risk for asthma 7 . Then we applied the four‐gene model among Chinese Han wheezing children and found that the high‐risk genotypes were associated with a positive Asthma Predictive Index and atopy 8 . In a word, the four‐locus gene model has been confirmed associated with asthma and atopy in Chinese Han children 7,8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation